Acute Gastroenteritis In Neonates In Relation To High Risk Infants - Immanuel Mustadjab; Muzief Munir; Suharno Suharno; F. H. Wulur (Indonesian Pediatric Society, 1984)
Acute gastroenteritis in neonates is more complicated than infantile gastroenteritis and the mortality rate is high especially in diarrhoeal outbreaks due to enteropathogenic escherichia coli (EPEC) infections. This study evaluated the epidemiological, clinical, bacteriological aspects and the mortality rate in relation to high risk infants. The incidence of diarhoeal diseases during a three year period (1975 -1977) was 4% ( 337 out of 8594 infants), specified as follows: -In 1975: 5.4% ( 160 out of 2967infants) - In 1976 : 3.6% ( 94 out of 2640 infants) - In 1977 : 3.1% ( 83 out of 2640 infants) Diarhoeal diseases most frequently occured in high risk infants, especially in low birth weights, neonatal asphyxia and pathologic labour. The high incidence of pathogenic bacteria was due to EPEC namely 32.2% (92 out of285 stool cultures).